Evaluación de la contaminación sonora por ruido vehicular motorizado en las principales vías de acceso del distrito de Nueva Cajamarca, provincia de Rioja - San Martín - Chota Loayza, Gary (2014)
This paper titled "Evaluation of noise pollution by motor vehicle noise on main roads in the district of Nueva Cajamarca province of Rioja, San Martin region" was aimed at determining the degree of noise pollution on main roads access in the district of Nueva Cajamarca For the development ofthis research is initiated by selecting the most critical points in the city ofNueva Cajamarca, of which a total of 40 points was chosen, then had to monitor 40 critica! points for a period of six months to achieve more reliable data using devices acoustic measurement (sound level meter), these results were calculated, averaged and arranged in cabinet to get the sound pressure level equivalent a-weighted (LAeqT) then be compared with those established in the rules of national environmental quality standards for noise (supreme Decree No. 085-2003-PCM). Shooting was performed and the UTM coordinates of the critics with the aid of a global positioning system (GPS) points are scored. After evaluating and contrasting the 40 points monitored with ACE-noise (residential area) could affirm and conclude that all points beyond the current rule, it is noteworthy that the highest point reached to 79.61 dB and low point carne to 67.76 dB, ifthese values are compared with the ACE-noise (shopping area) 34 points beyond the norm and only 6 are below it. Ifthese values are compared with the ACE-noise (industrial area) 100% of the points are below the current standard. Therefore it can be stated that vehicles circulating in the city are the main causes of noise pollution that exists in New Cajamarca. U sed the surfer 1 O software for mapping of noise, and 6 colors was determined for better viewing (green, lilac, purple, blue, yellow and red). Regarding the mitigation proposal clarifies that it will rely solely on the current authorities.